Development of the Pencak Sila Self-Protection Training Model Based on Character Education for Life Skills - Risa Marisatul Qibtiyah; Oman Hadiana (Indonesian Journal of Education Teaching and Learning (IJETL), 2025)
Study This aim develop training models martial arts martial arts based education character For increase life skills athletes , in particular aspect discipline and religiosity . The methods used is Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model . Subject study are 34 athletes teenager College Self Shield , selected in a way purposive of 62 athletes active . Model validation was carried out by two experts material and two practitioners use instrument Likert scale . Validation results show level very high eligibility with an average of 89%, covering suitability content , integration mark character , usefulness to life skills , and implementation in exercise . Implementation of the model produces improvement significant on the score discipline (+1.3) and religiosity (+1.3) based on observation before and after intervention . Findings This confirm that integration mark character to in exercise physique martial arts martial arts No only strengthen ability technical and tactical , but also form personality tough athlete​ in a way social and spiritual. This model recommended as alternative strategic in coaching sport based education holistic character .​